Comparative Dissolution Profiles of Branded versus Generic Clopidogrel Bisulfate: Assessing In Vitro Bioequivalence - Raisinghani, Prettish Kishore; Kristyawan, Fitri; Sholeh, Aries Badrus; Aliyansah, Pradip Iramdhan (Indonesian Journal of Life Sciences, 2025)
Clopidogrel, an antiplatelet agent widely prescribed for thromboembolic disorders, holds a substantial market presence in Indonesia, with a valuation of IDR 4.52 trillion. While plavix (branded form) remains as one of the leading treatments for such conditions, its high cost makes it unaffordable for a significant portion of Indonesia’s population. This underscores the necessity for generic alternatives that mimic the properties of the branded product to ensure broader accessibility and affordability for patients. To achieve this, generic clopidogrel bisulfate tablets must undergo the same crucial biopharmaceutical stages such as disintegration, drug release, aqueous dissolution, and systemic absorption to achieve therapeutic efficacy similar to the branded version. Despite being the most expensive tablet, the branded form serves as a standard reference to evaluate the dissolution profile, quality, and efficacy of locally manufactured generic formulations. This study investigates the dissolution profile and physical properties of generic clopidogrel bisulfate tablets produced by PT Phapros TBK, compared to a branded clopidogrel bisulfate product licensed by Sanofi in France. Quality attributes including weight and size uniformity, hardness, and disintegration time were assessed as per the Indonesian Pharmacopoeia (5th edition) standards. Dissolution tests were conducted at pH levels of 1.2, 4.5, and 6.8, with 12 sample replications at each interval, to determine bioequivalence between the two formulations. Through this research, the aim is to illuminate the bioequivalence of generic and branded clopidogrel products in Indonesia, offering insights into their interchangeability and potential clinical impact in a high-demand market.